Health Education on Diabetes Mellitus: Experience report (Research, Society and Development, 2024)
Objective: to report the experience of providing health education on diabetes mellitus for patients. Methodology: descriptive, qualitative, experience report type study on the development and execution of a health education activity on diabetes mellitus for users of a Municipal Health Unit in Belém do Pará. Green and red signs were used to streamline the health action. Results and Discussion: The concept and explanation of diabetes were given, as well as the types, symptoms, risk factors and epidemiology, normal values, possible complications of diabetes if not controlled and if appropriate behaviors are not adopted, such as kidney disease, diabetic foot, cardiovascular problems, ophthalmological problems, and others. In addition to providing information on ways to prevent these complications of diabetes, signs were distributed for a truth or myth dynamic with the signs, which received positive feedback. Health education actions using educational technologies help patients understand diabetes and adhere to self-care. Finally, people's doubts about diabetes were answered. Final Considerations: Therefore, the implementation of the health education activity received positive feedback from the community and contributed to the dissemination of information about Diabetes Mellitus.